Analisis Kepuasan Konsumen Terhadap Rumah Makan Vegetarian di Kota Pekanbaru - Liskawati Sihaloho; Evy Maharani; Roza Yulida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Vegetarian restaurants in Pekanbaru City has the advantage that might be presented in a fairly maximal effort such a strategic place, vegetables is the main menu with quite a lot of fans. The purpose of this research is to know the consumer perceptions and analysis the level of consumer satisfaction. This research was carried out at vegetarian restaurants Pekanbaru. Methods of analysis data using Importance Performance Analysis (IPA) and the Customer Satisfaction Index (CSI). The results of this research is attributes is need to be maintained on a consumer perception that science is based on attributes in quadrant B (the cooking spices, cuisine’s taste, the cleanliness menu, parking facilities, and knowledge of the waiter about the menu, menu presentation speed, cleanliness and tidiness of the room, toilet hygiene and cleanliness of the kitchen).  Attributes that should be fixed is in quadrant A (the size or portions food, intervals of payment and room decorating), and the customer’s level satisfaction with all  attributes of vegetarian restaurants by 83.20 percent through CSI analysis indicates that it totally is customers very satisfyied ranging from 0.80 to 1.00. Keywords: Perception, Consumer, Satisfaction, Vegetarian restaurants